Venomous Tongues : Speech and Gender in Late Medieval England - Bardsley, Sandy (Book collections on Project MUSE., 2006)
"The unique contribution of Venomous Tongues lies in its interdisciplinary approach and the way it situates scolding within a broader range of issues specific to the legal and social history of the period."--Leaf R. Poos, The Catholic University of America